(untitled) (JURNAL ADMINISTRASI PUBLIK, 2018)
This study aims To find out how the supervision on the implementation of aid programs construction of places of worship in the Village Wanga District Motoling Timur South Minahasa This research uses descriptive research method with qualitative approach. By applying a qualitative approach the authors have a wider opportunity in interacting with the object of research, so as to enrich and deepen the study in research that the author do Data Collection Techniques used some Interview techniques, Documentation study, Observation The results show the actual performance is smaller than the standard or in other words that what is done by the development commission in the congregation of GMIM Sion wanga village has not reached as expected Keywords: Supervision, Development Assistance Program Place of Worship